Low content Ru-incorporated Pd nanowires for bifunctional electrocatalysis. Issue 46 (26th August 2021) - Kweon, Yongdeog; Noh, Sunguk; Shim, Jun Ho
Abstract : The catalytic activity of Pd nanowires with low Ru contents showed superior bifunctional electrocatalytic performance towards both ORR and HER compared to the benchmarking Pt/C. Abstract : This paper reports the facile synthesis and characterization of carbon supported Pd nanowires with low Ru contents (nRuPd/C). An anti-galvanic replacement reaction involving the reduction of Ru(iii ) ions by nanoporous Pd nanowires to form nRuPd alloy nanowires was observed. A series of nRuPd/C materials with various Ru/Pd ratios were prepared by the spontaneous deposition of a Ru cluster on a Pd nanowire core using different Ru precursor concentrations (RuCl3 = 0.5, 1.0, 5.0 mM). The successful formation of low content Ru-incorporated Pd nanowires without individual Ru clusters were confirmed using physicochemical characterization. The electrocatalytic activity of the nRuPd/C for the oxygen reduction reaction (ORR) and hydrogen evolution reaction (HER) in alkaline media was measured by RDE polarization experiments. The electrocatalytic activity varied greatly depending on the Ru content on the Pd nanowires. Among the catalysts, the prepared Pd nanowires incorporated with a very small amount of Ru ( ca. 1.4 wt%) exhibited excellent electrocatalytic activity toward the ORR and HER: positive ORR/HER onset and E 1/2 potentials, higher n value, and lower Tafel slope.